1998
DOI: 10.1002/(sici)1097-4547(19980315)51:6<723::aid-jnr6>3.3.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Axonal regrowth through a collagen guidance channel bridging spinal cord to the avulsed C6 roots: Functional recovery in primates with brachial plexus injury

Abstract: Intraspinal implantation of a collagen guidance channel (CGC) to promote axon regeneration was investigated in marmosets with brachial plexus injury. After avulsion of the right C5, C6 and C7 spinal roots, a CGC containing (group B) or not (group A) a nerve segment, or a nerve graft (group C), was ventro-laterally implanted into the cord to bridge the ventral horn and the avulsed C6 roots. No spinal cord dysfunction was observed following surgery. Two months later, the postoperative flaccid paralysis of the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Among them, collagen material has been widely applied in SCI repair because of its abundance, good plasticity and great biocompatibility 30. Many types of collagen scaffolds have been tested to repair the SCI in animal models, including collagen tubes, fibers, membranes, and gels 31–35. It has been shown that the axons were regenerated and their functions were partially restored after collagen scaffold was grafted into the transected spinal cord.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, collagen material has been widely applied in SCI repair because of its abundance, good plasticity and great biocompatibility 30. Many types of collagen scaffolds have been tested to repair the SCI in animal models, including collagen tubes, fibers, membranes, and gels 31–35. It has been shown that the axons were regenerated and their functions were partially restored after collagen scaffold was grafted into the transected spinal cord.…”
Section: Introductionmentioning
confidence: 99%